2013
DOI: 10.1186/1471-2296-14-69
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety and stress symptoms among diabetics in Malaysia: a cross sectional study in an urban primary care setting

Abstract: BackgroundDiabetes mellitus is a highly prevalent condition in Malaysia, increasing from 11.6% in 2006 to 15.2% in 2011 among individuals 18 years and above. Co-morbid depression in diabetics is associated with hyperglycemia, diabetic complications and increased health care costs. The aims of this study are to determine the prevalence and predictors of depression, anxiety and stress symptoms in Type II diabetics attending government primary care facilities in the urban area of Klang Valley, Malaysia.MethodsThe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
122
5
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(151 citation statements)
references
References 56 publications
21
122
5
3
Order By: Relevance
“…Despite the high prevalence of diabetes in the general population in Malaysia (Institute for Public Health, 2011;Zanariah et al, 2010), only a few cohort or case-control studies are available on this topic. These studies support the hypotheses that people with diabetes are more likely to have depression or anxiety symptoms than people who do not have diabetes (Kaur et al, 2013;Subramaniam et al, 2009). Some authors have also suggested that depression and anxiety symptoms are significantly higher in postmenopausal women compared to premenopausal women (Saqsoz et al, 2001).…”
Section: Introductionsupporting
confidence: 62%
See 3 more Smart Citations
“…Despite the high prevalence of diabetes in the general population in Malaysia (Institute for Public Health, 2011;Zanariah et al, 2010), only a few cohort or case-control studies are available on this topic. These studies support the hypotheses that people with diabetes are more likely to have depression or anxiety symptoms than people who do not have diabetes (Kaur et al, 2013;Subramaniam et al, 2009). Some authors have also suggested that depression and anxiety symptoms are significantly higher in postmenopausal women compared to premenopausal women (Saqsoz et al, 2001).…”
Section: Introductionsupporting
confidence: 62%
“…Similarly, anxiety (31.8% versus 33.3%) and depression symptoms (20.9% versus 20.8%) as measured by the psychosocial domain of MENQOL were also similar for both groups, suggesting that attainment of menopausal status did not increase or decrease the psychological burden in participating women. A recent study in Malaysia (2013) found a relatively higher prevalence of depression and anxiety symptoms among people with diabetes (Kaur et al, 2013). This may be a result of differences in the screening instrument, the age groups (less than 35 and more than 75 years), and the inclusion of male participants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As DCNTs constituem grave problema de saúde pública, tanto em países ricos quanto nos de média e baixa renda, contudo estes últimos são os mais afetados, tendo em vista o escasso oferecimento de políticas públicas que modifiquem os determinantes sociais de saúde (MS, 2008 O estresse em pessoas com DM tende a estar presente desde o início da doença e em todo o seu curso (ORTIZ et al, 2011), uma vez que possuir uma doença crônica significa apresentar possíveis limitações ou incapacidades físicas (KAUR et al, 2013;ORTIZ et al, 2011;NASCIMENTO et al, 2010;CHAMORRO;MARTINEZ;TOMÁS, 2002). Dessa maneira, as pessoas podem sentir-se desanimadas com o plano terapêutico, preocupadas com o controle glicêmico e complicações, bem como apresentar dificuldades na proposição de metas concretas para o tratamento (ZULMAN et al, 2012).…”
unclassified